The first thousand words in Italian : with easy pronunciation guide - Amery, Heather; Di Bello, Patrizia; Cartwright, Stephen, 1947- (London ; Tulsa, Okla. : Usborne : EDC, 1983)
Captioned illustrations depict a basic vocabulary of Italian words.
3.2
3-6
Keywords: Italian language -- Vocabulary -- Juvenile literature; Italian language -- Readers -- Juvenile literature; Italian language -- Vocabulary; Italian language -- Readers; Vocabulary; Italian language